The capability of a construction project team in the implementation of a quality management system - Abdullah, Mat Naim (Penerbit UTM, 2008)
The concept of Quality Management System (QMS) is relatively new in the construction industry in Malaysia. It is however already existed since 1994 when in view of its importance to manage quality within this sector, the Government embarked on promoting the QMS to the construction organizations. QMS is defined as “all activities of the overall management function that determine the quality policy, objectives and responsibilities, and implement them by means such as quality planning, quality control, quality assurance and quality improvement within the quality system” [1]. It is believed that if the objectives of a firm are well defined and appreciated by all employees, the responsibilities of the department and the designation are clearly delineated and the procedures are well documented, it is likely that the products or services of the firm are “fit for purpose” and meeting the clients’ requirements. This is so important as for a company to remain viable it should meet the two essential factors i.e. to satisfy the client and to make profit. Evidences show that by adopting QMS, communications had been improved, mistakes, rework and wastage had been minimized, better control of subcontractors and suppliers etc., thus increasing productivity, profit and market share and meeting the client requirements [2,3]. Under the QMS for a specific project, the employer will forward his quality requirements to the employee. The activities, resources and events that will be deployed by the employee to meet the requirements for the specific project shall be written in a document called quality plan that provides a quality assurance to the employer and should be submitted before commencing the particular work.